Les quinze joyes de mariage : Conforme au manuscript de la bibliothèque publique de Rouen - La Sale, Antoine de; Jannet, Pierre, 1820-1870 (Salt Lake City, UT : Project Gutenberg, 2021)
"Les quinze joyes de mariage" by Antoine de La Sale is a satirical prose work published anonymously in the mid-15th century. Parodying a popular devotional text about the Virgin Mary's joys, this work presents fifteen darkly comic tableaux of marriage's "joys" actually its terrible misfortunes. Through vivid dialogues and realistic scenes, it depicts cunning wives, foolish husbands, and the supreme tragedy of losing one's freedom to matrimony's trap. Written in a lively, conversational style, each chapter unfolds as a mini-story exposing the pitfalls of married life with ironic amusement. (This is an automatically generated summary.)
Wikipedia page on this work: https://fr.wikipedia.org/wiki/Les_Quinze_Joies_de_mariage
Release date is 2021-05-07
Carlo Traverso, Laurent Vogel and the Distributed Proofreading team at DP-test Italia. (This file was produced from images generously made available by The Internet Archive/Canadian Libraries.)
Keywords: Women -- Humor; Marriage -- Humor; Women -- Early works to 1800; Marriage -- Early works to 1800; Satire, French